HF ISOTOPE CONSTRAINTS ON MANTLE EVOLUTION - Salters V.J.M.; White W.M. (My University, 1998)
The similarity of the Lu-Hf and Sm-Nd isotope system during most mantle differentiation processes makes the combination of 176Hf/177Hf and 143Nd/144Nd a very sensitive indicator of a select number of processes. This paper present new Hf-isotope data for a large number of ocean islands and examines the Hf-Nd-Pb isotope relations of oceanic volcanics. Except for HIMU islands, St. Helena and Tubaii, the Hf and Nd isotope ratios in ocean island basalts (OIB) are extremely well correlated. It is argued that crustal recycling (by either continental or oceanic sediments) most likely did not cause the Hf-Nd variations. The correlated 176Hf/177Hf-143Nd/144Nd variations in OIB most likely represent the time integrated fractionations which are the result of melting in the presence of garnet. The Hf-isotope systematics of HIMU-type OIB are consistent with these basalts representing recycled oceanic crust and thus support the earlier hypothesis on the origins of HIMU basalts. Chondrites form an array that is at high angle with the OIB array. This allows a choice in the 143Nd/144Nd and 176Hf/177Hf values for chondritic bulk earth. With a choice of bulk earth at the extreme end of the OIB array the shift of OIB to higher 176Hf/177Hf can be explained by either isolation of a significant amount of basalts from the mantle for several billions of year or by fractionation and isolation of small amounts (<1%) of perovskite, during the early history of the Earth. The large range in Hf-isotopes for a limited range in Nd-isotopes in MORB can be explained by addition of small amounts (#1%) of the perovskite material back into the MORB mantle. If chondritic BE is chosen to be internal to the OIB, the well correlated Hf-Nd isotope characteristics in OIB argue against the fractionation of perovskite during the early history of the Earth and the shape of the MORB field remains an enigma.
Keywords: HF ISOTOPE CONSTRAINTS; ISOTOPE CONSTRAINTS; MANTLE EVOLUTION